Intelligent Sensor for Measurement Systems with Sinusoidal Excitation Response - U. A. Mikitsevich; A. I. Svistun; A. V. Samarina; K. U. Pantsialeyeu; A. L. Zharin (Приборы и методы измерений, 2023)
Measuring devices and systems containing sensors that require sinusoidal excitation are widely used in information and measurement technology both in production conditions and in research practice. Examples include various types of metal detectors, eddy current flaw detectors, analyzers of liquid media, electrometers with a dynamic capacitor, etc. The aim of the work was to develop the optimal architecture and algorithms for the operation of intelligent sensors intended for use in measuring systems operating according to the sinusoidal excitation – response scheme.This paper describes the approach proposed by the authors to the construction of intelligent sensors based on modern microcontrollers, the distinctive feature of which is the continuous generation of sinusoidal excitation and reading responses in the background, as well as setting the readiness flags for data processing in the main process of the microprocessor, which ensures uninterrupted execution of background processes, the main of which is the generation of a sinusoidal excitatory action.This approach has been tested in the development of charge-sensitive surface mapping systems, such as the Kelvin probe based on a vibrating capacitor, and the surface photo voltage probe for the case of semiconductors.